The effect of filler loading and coupling agent on properties of Bentonite Filled Recycled High Density Polyethylene Composites - Muhammad Anas Husnan (School of Materials Engineering, University Malaysia Perlis, 2014)
Recycled high density polyethylene/ bentonite (RHDPE/Bentonite) composites had been prepared using BrabenderPlasticorder at temperature 160'C and rotor speed of 50 rpm. The effect of Bentoniteloadingand coupling agent on tensile properties, swelling behavior, morphology analysis, and spectroscopy infrared (FTIR) analysis on RHDPE/Bentonite composites were studied. The result showed that the addition of Bentonite reduced the tensile strength, elongation at breakand weight swell percentage of composites, whereas the Youngs modulus increased.